Cost-effectiveness of open vs. laparoscopic gastrectomy for locally advanced gastric cancer in China - Min Lai; YanTing Li; Ning Lan; Wenzhen Yuan (Scientific Reports)
Abstract Locally advanced gastric cancer (LAGC) poses a significant surgical challenge. While laparoscopic gastrectomy (LG) offers potential advantages, its cost-effectiveness relative to open gastrectomy (OG) in China remains uncertain. To compare the cost-effectiveness of LG and OG for LAGC in China. A Markov model compared the cost-effectiveness of LG and OG for LAGC. Probabilities and utilities were derived from published literature. Direct medical costs were obtained from the First Hospital of Lanzhou University. The primary outcome was the incremental cost-effectiveness ratio (ICER), expressed as the cost per quality-adjusted life-year (QALY) gained, using a willingness-to-pay threshold of ¥268,074/QALY. Sensitivity analyses assessed model robustness. Across 1-, 3-, and 5-year time horizons, OG had lower total costs and greater effectiveness than LG for LAGC. At 5 years, OG had a total cost of ¥128,259 and 7.20 QALYs versus LG’s ¥136,668 and 7.18 QALYs; the ICER for OG was -¥474,758/QALY. OG dominated at the ¥268,074 willingness-to-pay threshold. Sensitivity analysis indicated that variations in LG and OG costs minimally influenced the cost-effectiveness. Probabilistic sensitivity analysis, performed across 10,000 iterations, consistently identified OG as the optimal strategy (100% of iterations). From a Chinese health economics perspective—a framework essential for informing national healthcare resource allocation—OG consistently demonstrated a superior cost-effectiveness compared with LG for LAGC across 1, 3, and 5 years. This longitudinal observation of sustained cost-effectiveness persisted despite the statistically insignificant differences in overall costs and effectiveness between the two procedures.